God’s Place in Philosophy (Non in philosophia recurrere est ad deum) - Rescher, Nicholas (Philosophy & theology, 2000)
(1) Diametrically opposed standpoints can be maintained regarding God’s place in philosophy, namely that God has a central place here and, contrariwise, that philosophers should do their explanatory work without recourse to God. (2) The distinction between theistic and naturalistic issues is crucial here, because (3) the naturalistic sphere is substantially secular in orientation and is, in general, explanatorily closed. (4) A recourse to theistic considerations is not in order in the naturalistic domain insofar as the issues are local in character. (5) And since this in generally the case, the vast majority of philosophical issues admit of purely secular treatment. After all, philosophical theology is but a small part of philosophy. (6) Such localism is assured by considerations of explanatory economy. (7) What is at issue is not a matter of odium theologicum but simply of the rational procedure of beings whom God himself would surely want to make the fullest possible use of their God-given reason.